Whole genome sequencing of OXA-232-producing wzi93-KL112-O1 carbapenem-resistant Klebsiella pneumoniae in human bloodstream infection co-harboring chromosomal ISEcp1-based blaCTX-M-15 and one rmpA2-associated virulence plasmid - Tian, Chongmei; Xing, Mengyu; Zhao, Yaping; Fan, Xueyu; Bai, Yongfeng; Fu, Liping; Wang, Siwei (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives: To characterize one OXA-232-producing wzi93-KL112-O1 carbapenem-resistant Klebsiella pneumoniae (CRKP) co-harboring chromosomal blaCTX-M-15 and one rmpA2-associated virulence plasmid. Methods: Minimum inhibitory concentrations (MICs) were measured via broth microdilution method. Conjugation, chemical transformation, string test and Galleria mellonella infection model experiments were also conducted. Whole-genome sequencing (WGS) was performed on the Illumina and Nanopore platforms. Antimicrobial resistance determinants were identified using ABRicate program with ResFinder database. Insertion sequences (ISs) were identified using ISfinder. Bacterial virulence factors were identified using virulence factor database (VFDB). Wzi, capsular polysaccharide (KL) and lipoolygosaccharide (OCL) were analyzed using Kleborate with Kaptive. Phylogenetic analysis of 109 ST15 K. pneumoniae strains was performed using core genome multilocus sequence typing (cgMLST) on the Ridom SeqSphere+ server. MLST, replicons type, SNP strategies and another cgMLST analysis for 45 OXA-232-producing K. pneumoniae strains were further conducted using BacWGSTdb server. Results: K. pneumoniae KPTCM strain belongs to ST15 with wzi93, KL112 and O1. It possessed a multidrug-resistant (MDR) profile and was resistant to carbapenems (meropenem and ertapenem), ciprofloxacin and amikacin. Virulence assays demonstrated KPTCM strain possesses a low virulence phenotype. WGS revealed it contained one circular chromosome and 9 plasmids. The carbapenemase-encoding gene blaOXA-232 was located in a 6141-bp ColKP3-type non-conjugative plasmid and flanked by ΔISEcp1 and ΔlysR-ΔereA. Interestingly, blaCTX-M-15 was located in the chromosome mediated by ISEcp1-based transposon Tn2012. Importantly, it harbored a rmpA2-associated pLVPK-like virulence plasmid with iutA-iucABCD gene cluster and one IS26-mediated MDR fusion plasmid according to 8-bp (AGCTGCAC or GGCCTTTG) target site duplications (TSD). Based on the cgMLST and SNP analysis, data showed OXA-232-producing ST15 K. pneumoniae isolates were mainly isolated from China and have evolved in recent years. Conclusions: Early detection of CRKP strains carrying chromosomal blaCTX-M-15, OXA-232 carbapenemase and pLVPK-like virulence plasmid is recommended to avoid the extensive spread of this high-risk clone.